The Analysis of Medicine-taking Compliance Towards Therapy Outcome in Hypertension Patients at Community Health Centers in Yogyakarta Municipality - Rimanita Fortinasari; Dita Maria Virginia; Phebe Hendra (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2025)
Compliance to medication has a significant role in regulating the blood pressure and the risk for Atherosclerosis Vascular Disease (ASCVD) in Diabetes Mellitus Type 2 (DMT2) patients with hypertension as comorbidity. This study (n=523) aimed to analyzed this relationship at community health centers Yogyakarta municipality. We conducted an observational study with a cross-sectional design to analyze the medical record data collected during January-December 2023 among patients categorized under the inclusion criteria. Compliance was measured using the Medication Possession Ratio (MPR) then descriptively and correlatively with Chi-square analyses. No significant relationship is showed between the compliance of antihypertensive therapy to blood pressure (p=0.8670.05) and ASCVD risk (p=0.0800.05; OR=0.662; 95%CI:0.416-1.052). Age (p=0.001), gender (p=0.001) and BMI (p=0.0014) had a highly significant relationship with ASCVD risk, but only BMI (p=0.0070.005; OR 1.812) showed significant relationship with controlled blood pressure. The research findings reveal that compliance to antihypertensive therapy does not have a significant relationship with blood pressure control or ASCVD risk in patients with DMT2 and hypertension as comorbidities in Yogyakarta municipality. Highlighting the need for further investigation, it is vital to include other factors into blood pressure management.